New-onset diabetes after covid-19: mechanisms, metabolic implications, and clinical insights - Emad Al-Mulla; Baneen Sarhan Al-Bederi; Abtisam Faris Al-Shukry (Acta Chimica Asiana, 2026)
COVID-19 primarily affects the lungs, the impact of COVID-19 is not limited to the lungs only, but rather extends to affect other organs and body systems resulting in other complications that continue during the period of infection or beyond that. New onset diabetes and hyperglycemia is one of the complications of this virus. This study aims to investigate some biomarkers (HbA1c, triglycerides and cholesterol) in group of patients with post covid-19 syndrome and patient with post covid-19 hyperglycemia. Blood samples were withdrawn from 100 (50 controls including 25 males and 25 females and 50 patients including 25 males and 25 females) to investigate HbA1c, triglycerides and cholesterol levels. The result of the present study show that HbA1c significantly increased in PCS males (p.value=0.04) and in PCS females (p.value=0.05) in comparison with control males and control females respectively. The results also show that triglycerides have a significant elevation in PCS males (p.value=0.00) and PCS females(p.value=0.04) in comparison with control males and control females respectively. In the other hand cholesterol was non-significant in both groups. Correlation studies also included and show that there is no significant correlation between HbA1c and other measured parameters. Correlation studies also show that Triglycerides had a strong positive correlation with cholesterol in both PCS groups. Post COVID-19 hyperglycemia is a public health problem in concern and affect the body’s biochemical markers such as HbA1c and triglycerides reflecting their importance in monitoring the overall health in this group of patients.